Fitting in or standing out? The organisational socialisation of early career physical education specialism graduates through a micropolitical lens - Brennan, Cillian; Bowles, Richard; Murtagh, Elaine (European physical education review, 2025)
The recent emergence of primary school generalist teachers with physical education (PE) expertise has addressed calls for some form of specialisation in primary PE provision in Ireland ( Marron et al., 2018). It was hoped that these teachers could advance the quality of PE taught within schools, through their own teaching and by supporting colleagues ( Ní Chróinín, 2018). Despite PE specialism graduates (PESGs) developing teaching orientations and high self-efficacy to teach PE during their professional socialisation, it is unclear how their skills are applied within schools. This study examined the organisational socialisation of PESGs through a micropolitical lens, drawing on the research of Kelchtermans and Ballet (2002a, 2002b). Adopting a critical realist approach enabled us to explore teachers’ complex teaching realities. Semi-structured interviews were conducted with 11 graduates of the four-year Bachelor of Education with a major specialism in PE. Reflexive thematic analysis of interview data identified that PESGs had limited opportunities to apply their PE skills due to the conflicting custodial orientations of their schools. Due to PESGs’ professional interests, they were more likely to assimilate with the existing school culture as early career teachers, even if it overlooked their PE expertise. The outsourcing of PE provision to external coaches, and PESGs’ identity as novice teachers, also undermined their potential contribution as PE experts. Although some PESGs have positively used their knowledge to direct whole-school PE provision, more structured opportunities may be necessary to support the continued development of PESGs as teachers and leaders of PE.